Polarization Insensitive Ultra-Wideband ITO Coated PET Based Metamaterial Microwave Absorber - Krishangopal; Deepak Sood; Monish Gupta (International Journal of Engineering and Management Research, 2024)
In this paper, an ultra-wideband compact flexible polarization-insensitive metamaterial microwave absorber is proposed. Transparent PET (polyethylene terephthalate) was used as the dielectric substrate and ITO (indium tin oxide) is used as the conductor for the air and metamaterial structure. The intended absorber provides above 90% absorption in the range of 8.28 GHz to 17.18 GHz under normal incidence. The designed absorber exhibit 80% absorption at oblique angles of incidence. The unit cell size of designed absorber is 0.51λ × 0.51λ w.r.t the center frequency of absorption band. In addition, the designed structure is polarization insensitive absorber as it exhibit the same absorption performance in both TE and TM polarization under the normal incidence of the electromagnetic wave. The study was carried out as a simulation in the HFSS simulator. The results obtained were compared with other reference studies.